2008
DOI: 10.1074/jbc.m801214200
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein-associated Sphingosine 1-Phosphate Promotes Endothelial Barrier Function

Abstract: High density lipoproteins (HDL) are major plasma carriers of sphingosine 1-phosphate (S1P). Here we show that HDL increases endothelial barrier integrity as measured by electric cell substrate impedance sensing. S1P was implicated as the mediator in this process through findings showing that pertussis toxin, an inhibitor of G i -coupled S1P receptors, as well as antagonists of the S1P receptor, S1P1, inhibited barrier enhancement by HDL. Additional findings show that HDL stimulates endothelial cell activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
90
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(98 citation statements)
references
References 30 publications
6
90
0
Order By: Relevance
“…We first showed that, following apoA‐I treatment, Ldlr −/− mice have restored collecting lymphatic vessel integrity as shown by a decrease in Evans Blue leakage around the vessel, both with respect to the area and the perpendicular distance of leakage within the surrounding tissue. This is potentially reflected in previous studies where HDL was shown to increase endothelial barrier integrity, implicating sphingosine 1‐phosphate as a mediator 66. In our case, we suspected that apoA‐I acted in a similar way on the lymphatic vessels.…”
Section: Discussionsupporting
confidence: 67%
“…We first showed that, following apoA‐I treatment, Ldlr −/− mice have restored collecting lymphatic vessel integrity as shown by a decrease in Evans Blue leakage around the vessel, both with respect to the area and the perpendicular distance of leakage within the surrounding tissue. This is potentially reflected in previous studies where HDL was shown to increase endothelial barrier integrity, implicating sphingosine 1‐phosphate as a mediator 66. In our case, we suspected that apoA‐I acted in a similar way on the lymphatic vessels.…”
Section: Discussionsupporting
confidence: 67%
“…[16][17][18][19] Furthermore, HDL functions as a protective factor for the vascular endothelium by mechanisms that involve interactions with signaling receptors and hence go beyond the regulation of cholesterol homoeostasis or the inhibition of oxidation ( Figure 1). HDL induces endothelium-dependent vascular relaxation via increased endothelial nitric oxide synthase (eNOS) phosphorylation and nitric oxide production, 20 and maintains endothelial barrier stability by promoting endothelial cell survival, 21,22 stimulating endothelial junction closure via HDL-bound sphingosine-1-phosphate (S1P), 23,24 and accelerating endothelial cell migration and re-endothelialization of injured arteries. 25,26 Moreover, antiinflammatory activities of HDL in atherosclerosis have been documented.…”
Section: Hdl and Protection Against Cardiovascular Diseasementioning
confidence: 99%
“…49 Total protein and apoA-I concentration was determined using Pierce BCA Protein Assay Kit and apoA-I ELISA as described above.…”
Section: Preparation Of Human Plasma Hdl Subfractionsmentioning
confidence: 99%